ANALISIS MODEL PENILAIAN KINERJA PELATIHAN KONSTRUKSI DI INDONESIA (Universitas Esa Unggul, 2016)
The provision of infrastructure is a key factor in the growth and equity of the region's economy. If infrastructure services are carried out reliably in different parts of Indonesia then other sectors, such as education, trade, health and others will grow rapidly. Mainstreaming the provision of this infrastructure makes development activities across Indonesia increase very quickly. It is also supported by the development of good construction technology, so it takes also skilled and skilled construction workers to compensate for these technological advances. Knowing how the mechanism of implementation of construction workforce training in Indonesia today. Identify indicators and parameters of training performance appraisal components. The data were obtained by visiting / observing directly on ongoing construction training and interviewing with stakeholders. Indicators for improving the quality of labor construction training in Indonesia, among others, the ability of instructors in delivering materials and teaching methods used, the suitability of the material to the current state of construction and the commitment of participants to the implementation of the training other than that the application of certification exam to the participants / construction workers should be done continously.Â Keywords: infrastructure, construction, labor, performance appraisal model, system theory